Estimation of power performances and flow characteristics for a Savonius rotor by vortex particle method - Pan, Jingna; Ferreira, Carlos; Zuijlen, Alexander (Wind energy (Chichester, England), 2023)
This study investigates the implementation of the vortex particle method (VPM) with the goal of efficiently and accurately estimating the power performances and flow characteristics for a Savonius rotor. The accuracy and efficiency of simulation methods are critical for the reliable design of Savonius rotors. Among various approaches, VPM is chosen because it can be flexibly incorporated with self‐correction techniques, and the distribution of bound vortex particles can effectively represent complex geometries. In this work, a double‐trailing‐edge‐wake‐modeling vortex particle method (DTVPM) is presented to extend the working range of VPM for dealing with large rotating amplitudes and high tip speed ratios (TSRs). DTVPM addresses asymmetrical torque predictions for a Savonius rotor without gap width. However, DTVPM performs poorly at high TSRs due to the absence of viscous effects near the surface. To capture complex wake structures, such as reverse flow structures, the viscous correction for tip vortices is suggested. The current research focuses on the implementation and validation of DTVPM for predicting torque coefficients and wake patterns, as well as comparisons to OpenFOAM results. Two‐dimensional and incompressible flow is estimated at λ = 0.2–1.2. For the studied cases, a maximum power coefficient is obtained at λ≈0.8, consistent with published experimental data. In addition, the process of trailing‐edge vortices generation and detachment is captured by DTVPM. The comparison results between OpenFOAM and DTVPM show that DTVPM allows to efficiently simulate a Savonius rotor without any empirical parameters. DTVPM will help to improve existing engineering models for wind energy fields.